THE EFFECTS OF PHOTOPERIOD MANIPULATION ON MORPHO-ANATOMY AND GROWTH OF Clarias gariepinus - Sandra Lubis; Windarti Windarti; Morina Riauwaty (Berkala Perikanan Terubuk, 2018)
Changing in photoperiod duration will affects the physiology of fish in general. A study aims to understand the effects of photoperiod manipulation towards C. gariepinus morpho-anatomy and growth was conducted on March–May 2018. The fishes were reared in fiber tanks (140 x 60 x 40 cm) that was filled with water and completed with a circulatory system. Treatments applied were Control (natural photoperiod), 24G (24 hours dark), 18G6T (18 hours dark and 6 hours light), and 6G18T (6 hours dark and 18 hours light). The fishes were sampled once/14 days, 4 fishes/ aquarium/sampling. Parameters measured were length-weight relationship, condition factor, hepatosomatic index (HSI), viscerasomatic index (VSI), absolute length and weight, food conversion ratio (FCR), gonad development and body protein/fat. Results shown that photoperiod manipulation affects C. gariepinus morpho-anatomy and growth. The highest growth parameters and morpho-anotomy index were found in fish reared in 18G6T. By the end of the experiment, the b value of   length-weight relationship was 3.3205, absolute weight and length were 86.70 g and 17.23 cm, condition factor was 0.84, VSI was 25.31%, HSI was 11.42%, FCR was 1.43, and body protein and fat was 48.40% and 50.38%. In the fish reared in 24G treatment, b was 1.9262, 52.13 g BW and 14.19 cm SL, condition factor was 0.80, VSI was 23.30%, HSI was 9.38%, FCR was 2.47, and body protein and fat was 48.08% and 49.53%. In the fish reared in 6G18T, b was 2.6903,49.45 g BW and 13.79 cm SL, condition factor was 0.79, VSI was 23.30%, HSI was 6.80%, FCR was 1.91, and body protein and fat was 46.64% and 49.00%. Fish reared in natural photoperiod (control) shown the lowest results b was 2.0418, 51.68 g BW and 14.21 cm SL, condition factor was 0.79, VSI was 19.58%, HSI was 6.96%, FCR was 2.20, and body protein and fat was 43.95% and 47.77%.Early developing gonad (1st maturity stage) was only found in fish reared in 18G6T. Based on data obtained it can be concluded that the photoperiod manipulation affect the morpho-anatomy and growth of C. gariepinus.